2016
DOI: 10.18671/scifor.v44n111.21
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de espécies de Bambu como fonte energética

Abstract: ResumoO objetivo do presente trabalho foi o de avaliar as características da biomassa e do carvão vegetal das espécies Bambusa tuldoides, Bambusa vulgaris var. vittata e Dendrocalamus asper visando determinar o seu potencial para o uso energético. Para fins comparativos, foram utilizadas árvores de híbridos de Eucalyptus grandis x Eucalyptus urophylla com 6 anos. A biomassa das espécies foi caracterizada (densidade básica, análise imediata, poder calorífico superior e densidade energética) e foi produzido carv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 5 publications
6
15
2
3
Order By: Relevance
“…Santos et al (2016) reported a basic density value of 0.604 g cm -3 for D. asper, in accordance with our results. However, the density of B. vulgaris (0.462 g cm -3 ) and B. tuldoides (0.421 g cm -3 ) observed here differ from those reported by Santos et al (2016).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Santos et al (2016) reported a basic density value of 0.604 g cm -3 for D. asper, in accordance with our results. However, the density of B. vulgaris (0.462 g cm -3 ) and B. tuldoides (0.421 g cm -3 ) observed here differ from those reported by Santos et al (2016).…”
Section: Resultssupporting
confidence: 93%
“…According to Brito et al (1987), the basic density of the tissues of bamboo species of the Guadua genus may reach 0.45-0.65 g cm -³, with Guadua angustifolia having a density of 0.629 g cm -³. Santos et al (2016) reported a basic density value of 0.604 g cm -3 for D. asper, in accordance with our results. However, the density of B. vulgaris (0.462 g cm -3 ) and B. tuldoides (0.421 g cm -3 ) observed here differ from those reported by Santos et al (2016).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations